KERAGAMAN GENETIK HlBRIDA BEBERAPA STRAIN IKAN NILA {Oreochromis niloticus Bleeker) - Rudhy Gustiano; Dinar Soelistyowati; Agung Luthfi Fauzan; Otong Zenal Arifin (BERITA BIOLOGI, 2011)
Objectives of this study are to determine the genetic variability among progeny of intraspecific crossing between three strains of Oreochromis niloticus Bleeker (BEST, Nirwana, and Red NIFI) using Randomly Amplified Polymorphic DNA (RAPD) and truss morphometric. The results showed that hybridization enabled to increase genetic variability respectedly on progeny of Nirwana male crossed to BEST female (27,93%) as well as to Red NIFI female. An analysist of truss morphometric indicated that BEST population had the lowest similarity and largest genetic distance (0,6) to the Nirwana and Red NIFI which were closer to the hybrid populations.